Theoretical and experimental research of tiling error compensation method based on a small-size mirror for large-aperture tiled-grating compressors. (August 2018) - Zhang, Sen; Zhang, Junwei; Wang, Yin; Wang, Xiao; Feng, Xi; Mu, Jie; Xiang, Xiangjun; Lin, Donghui; Su, Jingqin; Li, Zhilin; Zhou, Yi
Highlights: A compensation method of tiling error for large-aperture tiled-grating is proposed. Compensation effects on spatial and temporal performance are analyzed. Tiling errors tolerances are increased many times than traditional method. Experimental results have proved the method to be of validity. Abstract: Tiled-grating techniques have been adopted in many multi-kilojoule petawatt laser facilities to meet the size requirements for compression gratings. To realize coherent tiling, we propose a new simple method of tiling error compensation for large-aperture tiled-grating compressors. In this method, errors are controlled by adjusting a small-size mirror. We theoretically analyze that this method improves errors tolerances many times higher than that of traditional compensation method and approaches the limit of adjustment accuracy. An experiment also has been carried out to demonstrate the feasibility. The method significantly reduces the difficulty of tiling, increases the stability of large-aperture tiled-grating compressor system and could be applied to coherent combination of large-aperture short laser beams.